Analysis of the Level of Satisfaction of Broiler Plasma Chicken Breeders with the Implementation of Partnerships with Core Companies in Kendari City - Dedu, La Ode Arfan; Batoa, Hartina; Alwi, La Ode; Gafaruddin, Abdul; Sudarmo, Hadi; Nur, Hartatia; Padangaran, Normal Bivariant (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2024)
This research aims to analyze the level of satisfaction of broiler chicken plasma farmers regarding the implementation of partnerships with core companies in Kendari City. This research was carried out in June - July 2023, and the research location was Kendari City because many broiler chicken plasma farms partner with core companies. The data types consist of primary data and secondary data. Data collection techniques used include interview techniques and literature. Calculations were carried out to find an index of farmers' satisfaction levels with: (a) production facility services, (b) cultivation technical services, and (c) post-harvest services by determining weights based on the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The research results show that the Importance Performance Analysis (IPA) attribute included in quadrant I is the adequacy of production facility services and guidance materials, as well as the suitability of harvest time. Attributes included in quadrant II are DOC quality, feed quality, adequacy of medicines and vaccines, frequency of technical guidance, and time for payment of harvest results. The attributes in quadrant III are DOC prices, feed prices, drug and vaccine prices, production facility delivery schedules, and handling of remaining sapronac. The attributes in quadrant IV are responses to complaints and the suitability of output prices. Based on the Customer Satisfaction Index (CSI) analysis, the farmer satisfaction level is 0.722 or 72.20 percent, which falls into the satisfied categor